Internalization of Islamic Values in Children within Families in the Digital Era - Aziz, Thorik (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The digitalization of a wide range of information poses a significant challenge in the current era, especially concerning the integration of Islamic values in early childhood education. This research delves into the Islamic education of young children within familial settings during the digital age, utilizing a